Therapeutic effects of probiotics on symptoms of irritability/emotional lability associated with neurodevelopmental conditions: A systematic review and meta-analysis of placebo-controlled trials - Ping-Wen Huang; Chen Chia-Min; Cheuk-Kwan Sun; Yu-Shian Cheng; Yen-Hsiang Tang; Cheng Liu; Kuo-Chuan Hung (Complementary Therapies in Medicine, 2025)
Objectives: The current study aimed at investigating the efficacies of probiotics in alleviating the symptoms of irritability/emotional lability in individuals with a neurodevelopmental condition. Methods: Randomized placebo-controlled trials were identified through searching major electronic databases from inception to December, 2023. The outcome of interests included improvements in the symptoms of irritability/emotional lability. Outcomes were quantitatively expressed as effect size (ES) based on standardized mean difference (SMD) with 95 % confidence interval (CI). Results: Seven studies with 1479 participants were included in this meta-analysis. The primary results revealed a significant improvement in the symptoms of irritability/emotional lability in individuals with neurodevelopmental conditions receiving probiotics compared with the placebos (SMD= −0.17, p = 0.03). Subgroup analyses demonstrated an association between a significant improvement in the symptoms of irritability/emotional lability and the use probiotics relative to placebos only in studies using multiple-strain probiotics (SMD=-0.19, p = 0.04, three studies with 452 participant) but not in those adopting single-strain regimens. Conclusions: Our study supported the use of probiotics for alleviating the symptoms of irritability/emotional lability in individuals with neurodevelopmental conditions, mainly in those receiving multiple-strain probiotics as supplements. Nevertheless, the limited number of studies targeting irritability as their primary outcomes, and most did not investigate other confounding factors such as dietary habits or consumption of other nutritional supplements may impair the robustness of evidence. Our results, which were derived from a limited number of available trials, warrant further large-scale clinical investigations for verification.